Intervenciones de enfermería para el cuidado del paciente con traqueostomía: revisión sistemática - Arciniega Márquez, Pamela Cristina (2025)
Introduction: Tracheostomy is a procedure where a hole is made in the wall of the trachea. It is indicated when the airway is compromised. The two techniques performed are surgical and percutaneous, the latter being more beneficial as it reduces difficulties. The complications may include bleeding, stenosis, infection, and decannulation, among others. The main nursing care includes suctioning secretions, stoma care, and psychosocial care. Objective: To describe nursing interventions for patients’ care with tracheostomy through a systematic review. Methods and Techniques: The research is a systematic review. A qualitative approach was used for the interpretation and analysis of the documents. The scope was descriptive. The PRISMA method was used. Results: The main results showed that patients with mechanical ventilation have a higher requirement for tracheostomy. The percutaneous technique has greater benefits compared to the surgical technique. The most common complications are bleeding and stenosis. The main nursing care includes suctioning secretions, cleaning and peristomal care, patient and caregiver education, and psychosocial interventions. Conclusions: Tracheostomy is crucial for patients with compromised airways, with the percutaneous techn ique being preferred due to its fewer complications. Suctioning secretions and self-care education are essential to prevent complications and improve the patient’s quality of life.